The Long Shadow of Slavery: The Persistence of Slave Owners in Southern Law-Making - Luna Bellani; Anselm Hager; Stephan Maurer (Institute of Labor Economics (IZA), 2020)
This paper documents the persistence of the Southern slave owning elite in political power after the end of the American Civil War. We draw on a database of Texan state legislators between 1860 and 1900 and link them to their or their ancestors' slaveholdings in 1860. We then show that former slave owners made up more than half of nearly each legislature's members until the late 1890s. Legislators with slave owning backgrounds differ systematically from those without, being more likely to represent the Democratic party and more likely to work in an agricultural occupation. Regional characteristics matter for this persistence, as counties with higher soil suitability for growing cotton on average elect more former slave owners.
Keywords: D72; J62; N31; H4; 330; wealth inequality; elites and development; US South; intergenerational persistence; slavery